CLIL IN PRACTICE, ACHIEVEMENTS AND DRAWBACKS, AND FUTURE IMPLICATIONS (Web of Teachers: Inderscience Research, 2024)
Content and Language Integrated Learning (CLIL) has gained momentum globally as an educational approach that promotes language acquisition alongside subject knowledge. This article examines the practical implementation of CLIL, analyzing its achievements, drawbacks, and future implications. Through a comprehensive literature review and discussion of methods, results, and implications, the study provides insights into the effectiveness and challenges of CLIL in diverse educational settings.